Allan Boesak, Black Theology and Apartheid: : A theological-historical approach - Fortein, Eugene (Stellenbosch Theological Journal, 2018)
In this article I will give specific attention to the reciprocal relationship between Black Theology and Allan Boesak based on his lived experience of apartheid from a theological-historical perspective. It is my presupposition that Boesak's experience of apartheid made him prone to the influence of Black Theology and that he in turn adapted American Black Theology so that it could be made applicable to the South African context. Black Theology unlocked an entire new theological paradigm for Boesak which enabled him to speak prophetically to the challenges and injustices that occurred under apartheid in South Africa. Attention will be given to the emergence of Black Theology in South Africa, how Boesak was challenged by it and how Black Theology, through Boesak, impacted the theological landscape.